2022
DOI: 10.30773/pi.2022.0179
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic and Social Distancing on Cognition of Alzheimer’s Disease Patients

Abstract: Objective The risk of rapid cognitive decline in Alzheimer’s disease (AD) during the coronavirus disease 2019 (COVID-19) pandemic has been recognized. The purpose of this study was to investigate the cognitive decline in such patients during the COVID-19 pandemic by evaluating changes in their cognitive measure parameters before and after the pandemic.Methods This was a retrospective cohort study conducted in AD patients during their first visit and one-year regular follow-up for testing cognitive function at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Recently, the coronavirus disease 2019 (COVID‐19) pandemic proved to be an opportunity to study the effect of social isolation on cognitive decline. Two studies found an accelerated cognitive decline in patients with dementia following the start of the pandemic 41,42 . Similar analysis could be performed on a cognitively intact older population to study the effect of social isolation on incident dementia.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, the coronavirus disease 2019 (COVID‐19) pandemic proved to be an opportunity to study the effect of social isolation on cognitive decline. Two studies found an accelerated cognitive decline in patients with dementia following the start of the pandemic 41,42 . Similar analysis could be performed on a cognitively intact older population to study the effect of social isolation on incident dementia.…”
Section: Introductionmentioning
confidence: 93%
“…Two studies found an accelerated cognitive decline in patients with dementia following the start of the pandemic. 41,42 Similar analysis could be performed on a cognitively intact older population to study the effect of social isolation on incident dementia. Introduction of a new law or changes in guidelines automatically affect an entire population, yielding large sample sizes and eliminating selection bias.…”
Section: Interrupted Time Seriesmentioning
confidence: 99%
“…Data on the severity, susceptibility, and hospitalization of COVID-19 showed that COVID-19 may increase the risk of AD [88,89]. Other research also indicates that AD seems to be particularly associated with SARS-CoV-2 infection among neurodegenerative diseases [90][91][92][93][94]. It is important to note that research in this area is ongoing, and the long-term outcomes of COVID-19 and its complications might not be known for decades.…”
Section: Sars-cov-2mentioning
confidence: 99%